Analysis of goal scoring patterns in the UEFA Women`s EURO 2022 - Sanmiguel Codina, J.; Ballester Lengua, R.; Casal, C. A.; Huertas Olmedo, F. (Biology of Sport, 2025)
Despite the growing interest in research on women`s football, few approaches have analysed the primary performance indicator in football, which is the goal. This study describes the goal scoring patterns and explores technical-tactical behaviours associated with the scorer location in the 2022 UEFA Women`s European Championship. The sample was made up of all the 95 goals scored by the 16 teams in the 31 games played. Three UEFA Pro coaches designed an ad hoc observational instrument, and one observer coded the data after a training process, ensuring intraobserver reliability. Descriptive and inferential analyses were conducted. Assistant location was significantly associated with scorer location (p < 0.005, ES = 0.930). The highest percentage of assists came from the lateral corridors outside the penalty area (23.2%). The most frequent shot zones being the projection from the goal line to the penalty spot (48.2%). It is also remarkable that half of the goals came from an aerial ball (51.2%), the leg (66.3%) and a first contact shot (69.8%) being the most common finishing situations. A similar distribution was noted concerning the areas where shots crossed the goal line (40.0% near post vs 41.3% far post). Our findings reveal goal-scoring patterns in elite women`s football to consider in the coaching process, for instance, to design drills to promote the replication of the most common finishing situations (aerial, leg and first contact) and contexts where most recurrent assisting and shooting zones could be considered. Raising awareness among coaches and players about these practical aspects can improve goal scoring situations.